Bulk Viscous String Cosmological Model With and Without Magnetic Field: Impact of Bulk Viscosity and Magnetic Field on String Cosmological Model (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The present paper provides solution for Bianchi type-III string cosmological model is presence of bulk viscosity with and without magnetic field using different conditions like equation of state and an assumption that the scalar of expansion is proportional to the shear scalar which leads to the relation between metric potentials where to A, B, C, D and n are constants. The physical and geometrical aspects of the models are also discussed in presence and absence of magnetic field.